A Ruthenium-Catalyzed C–H Activation Strategy as an Efficient Shortcut in the Total Synthesis of 6,8-Dimethoxy-1,3-dimethylisoquinoline - Fonzo, Santiago; Vargas, Didier F.; Kaufman, Teodoro S. (Synthesis, 2019)
A short and convenient total synthesis of 6,8-dimethoxy-1,3-dimethylisoquinoline, employing a C–H activation/alkenylation strategy, is reported. The approach involves the CeCl3·7H2O-promoted methoximation of 2,4-dimethoxyacetophenone and a methoxime-directed ruthenium-catalyzed allylation. This was followed by a one-pot, ruthenium-catalyzed allyl to propenyl isomerization and a microwave-assisted 6π-azaelectrocylization to complete the sequence. This approach, which entails a shortcut in the synthetic management of the three-carbon side chain, is an improved and more efficient route toward the natural product, which facilitated its access in just three steps and 27.3% overall yield.
Keywords: C–H activation; one-pot transformation; total synthesis; natural product; ruthenium catalysis; 6,8-dimethoxy-1,3-dimethylisoquinoline